Pattern of Aluminum-Induced Secretion of Organic Acids Differs between Rye and Wheat - Li, Xiao Feng (American Society of Plant Physiologists, 2000)
Al-Induced secretion of organic acids from the roots has been considered as a mechanism of Al tolerance, but the processes leading to the secretion of organic acids are still unknown. In this study, the secretion pattern and alteration in the metabolism of organic acids under Al stress were examined in rye (Secale cereale L. cv King) and wheat (Triticum aestivum L. cv Atlas 66). Al induced rapid secretion of malate in the wheat, but a lag (6 and 10 h for malic and citric acids, respectively) between the exposure to Al and the secretion of organic acids was observed in the rye. The activities of isocitrate dehydrogenase, phosphoenolpyruvate carboxylase, and malate dehydrogenase were not affected by Al in either plant. The activity of citrate synthase was increased by the exposure to Al in the rye, but not in the wheat. The secretion of malate was not suppressed at low temperature in the wheat, but that of citrate was stopped in the rye. The Al-induced secretion of citrate from roots of the rye was inhibited by the inhibitors of a citrate carrier, which transports citrate from the mitochondria to the cytoplasm. All of these results suggest that alteration in the metabolism of organic acids is involved in the Al-induced secretion of organic acids in rye, but only activation of an anion channel seems to be responsible for the rapid secretion of malate in the wheat.